Karakteristik campuran abu sekam padi dan slag sebagai cementituous materials - Irma Aswani Ahmad; Heru Winarno; Andi Yusdy Dwiasta (Seminar Nasional LP2M UNM, 2019)
Raw material in cement production is a source of natural wealth that is not renewable, namely limestone, silica sand, clay and iron sand. This situation causes the cement productions damage environmental sustainability. Based on this phenomenon, the researchers tried to find other materials that are like cement (cementitious material). According to previous researchers, rice husk ash and slag contain silica in sufficient quantities so that it can be used as a substitute for cement. Therefore the purpose of this research is to use both organic and inorganic waste materials as cementitious materials that are like cement. The research conducted was experimental research. Rice husk ash and slag as cementitious material are examined for chemical characteristics and physics. Test specimens in the form of cement paste are divided into two types, namely control specimens (without rice husk ash and slag) and treatment specimens (husk ash and slag as much as 2.5% - 15% of the weight of cement). Tests performed on cement paste are normal consistency and setting time. Based on the results of normal consistency and setting time, the mixture of rice husk ash and slag can be categorized as cementitious material.